HAKIKAT LITERATURE REVIEW DALAM PENELITIAN BIMBINGAN DAN KONSELING - Fatheni Cova Kamil Khairy; Mardhatillah; Wahidah Fitriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The literature review plays a strategic role as a theoretical foundation in formulating research problems, determining research directions, and building a strong conceptual framework. This study aims to describe and analyze the nature of the literature review in guidance and counseling research, to emphasize its important role in strengthening theoretical foundations, improving research quality, and encouraging the development of evidence-based counseling practices. The method employed is a qualitative approach using a library research design. The findings indicate that the literature review is essential in research, including guidance and counseling studies, as it functions as a theoretical foundation that strengthens the research conceptual framework, identifies research gaps (novelty), and reinforces academic arguments as well as research relevance. Therefore, the preparation of a guidance and counseling thesis is a scientific process that determines research quality, relevance, and contribution to the field.